PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI KANTOR KECAMATAN TASIK PUTRI PUYU - Hendra; Woro Utari; C. Sri Hartati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The target of this research is as a tool to find out and analyze the impact of compensation, work environment, leadership on job satisfaction. This type of research is explanatory research and uses a quantitative approach. The population in this study were all 32 employees of the Tasik Putri Puyu Sub-District Office and using a census sampling of 31 people because the researchers were reduced. The method of analysis that will be applied in this research is to use multiple linear regression analysis. The research found that compensation, work environment, leadership and employee satisfaction at the Tasik Putri Puyu District Office were good. Compensation and leadership have a positive and significant impact on employee satisfaction. work environment has a positive but not significant impact on employee satisfaction.